Pengaruh Metode Demonstrasi terhadap Pemahaman Siswa dalam Pembelajaran Fiqh konteks Ibadah - Makhrus Khalim Al Afghani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Education has a major role in the process of forming the character, ethics and morals of Gen-Z or the current generation. The subject that reflects several Islamic values is Fiqh. Students' understanding or interest in Fiqh subjects is still not optimal. So it is necessary to apply effective learning methods to increase student understanding. The demonstration method is one approach that is very suitable for achieving this goal. Because, students have the opportunity to see firsthand how the concepts in Fiqh can be applied in worship as well as everyday life . The process begins with a planning stage carried out with the teacher to identify various fiqh concepts that are confusing and often difficult for students to understand. Then there is a live demonstration where students actively participate in learning through observation and asking questions. Then the data was collected through interviews and observations of students, and qualitative analysis was carried out. Implementation will be greatly supported by the presence of materials or tools such as printed Fiqh of Worship books, visual presentation tools, animated videos and other multimedia support, while the instruments are still guided by interviews and observations . The demonstration method makes an important contribution to the development of students in critical thinking and solving problems, developing ethics and understanding related to worship in Fiqh. By formulating solutions, the ability to analyze problems, and also make ethical decisions. The right step in improving the development of the quality of Islamic religious education in the field of Fiqh in the context of worship is to use the demonstration method, because in this method, students will easily understand several concepts of worship in Fiqh by being more involved in learning and better.